Artikulasi Kekuasaan Dalam Masyarakat Nelayan: Studi Kasus Klientelisme di Pesisir Kota Makassar - Rizari Rizari; Sudarmono Sudarmono; Hari Hari (Institut Pemerintahan Dalam Negeri, 2020)
Abstract The patron-client relationship had been emerged as it embedded in social relation of production among fishing community. This article is attempt to explain the articulation of patron-client relationship that emerged among coastal fishing community in Makassar City. Qualitative method was used to collect data. Mostly, ethnographic approach was used to identified and observe the articulation of power realtion. This study has discover that patron client is not merely exist in social economy activities. Contemporary issue also indicates that this dynamic has also interfered the power relationship among coastal fishing community. Keyword: power relationship, patron client, fishing community